Costs of undernutrition in Pakistan - Saeed, Wajiha; Davies, Stephen; Shahzad, Saqib; Moeen, Muhammad Saad (International Food Policy Research Institute, 2018)
Undernutrition leads to large monetary costs to an economy, which come most directly from higher mortality/premature death, a higher incidence of illnesses, and lower productivity due to nutritional deficiencies. Undernutrition among children also contributes to costs in the education system due to poorer performance at school and hence more grade repetitions and lower educational levels. These outcomes result in an estimated total economic cost of as much as Rs. 704.3 billion (Table 1) resulting from losses of earnings/productivity, health costs, and education costs. The following describes the estimation of these costs.